ANALISIS PENGARUH HARGA, KUALITAS PRODUK, KEBUTUHAN MENCARI VARIASI DAN IKLAN PRODUK PESAING TERHADAP KEPUTUSAN PERPINDAHAN MEREK PADA KONSUMEN PEMBALUT WANITA CHARM (Survei pada Mahasiswi Fakultas Ekonomi Universitas Slamet Riyadi Surakarta) - Debora Ocvia Arundina, Untung Sriwidodo & Edi Wibowo (Universitas Slamet Riyadi, 2016)
The large number of brands of sanitary napkins that are on the market causing consumers desirability has moved from one brand to another brand. The shift of consumers to other brands is influenced by various factors, including price, product quality, needs looking for variety and product advertising competitors. The purpose of this research was: analyzing the significance of the influence of prices, quality products, needs looking for variety and product advertising a competitor against the decision of the transfer of the brand on consumers ' sanitary napkins Charm Coed Faculty of Economics University of the Slamet Riyadi. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this study all Coed Faculty of Economics University of Surakarta Slamet Riyadi force 2012-2015 to ever use sanitary napkins Charm. The number of samples that used as many as 70 students with techniques of sampling using a purposive sampling. Methods of data collection were used: questionnaires, observation and documentation. Technique of data analysis used the test of validity, reliability test, test the assumption of Linear regression analysis, classic Double, t test, F test, and the coefficient of determination. The research results obtained conclusions: 1) there is a significant influence on the price of the transfer of the brand on consumers ' sanitary napkins Charm Coed Faculty of Economics University of the Slamet Riyadi. 2) there is a significant influence on the product quality of the transfer of the brand on consumers ' sanitary napkins Charm Coed Faculty of Economics University of the Slamet Riyadi. 3) there are significant effects needs looking for variation of the displacement of the brand on consumers ' sanitary napkins Charm Coed Faculty of Economics University of the Slamet Riyadi. 4) there is a significant influence of advertising products of competitors against the decision of the transfer of the brand on consumers ' sanitary napkins Charm Coed Faculty of Economics University of the Slamet Riyadi.Keywords: pricing, quality products, needs looking for variety, advertising products of competitors, brand switching